Development and validation of assessments of adolescent health literacy: a Rasch measurement model approach. - Fleary, Sasha A.; Freund, Karen M.; Nigg, Claudio R. (Tufts University. Tisch Library., 2022)
Keywords: Adolescents, Health literacy, Measurement, Health communication.; Springer Open.